1994
DOI: 10.1016/0014-5793(94)80281-5
|View full text |Cite
|
Sign up to set email alerts
|

The atomic structure of Carnation Mottle Virus capsid protein

Abstract: The structure of the Carnation Mottle Virus (CMtV) capsid protein has been determined at 3.2 A resolution by the method of molecular replacement. Three-dimensional data were collected from a small number of crystals (sp.g. I23, a = 382.6 A) using the synchrotron radiation with an image plate as detector. The coordinates of Tomato Bushy Stunt Virus (TBSV) were used as a searching model. Refinement of the coordinates of 7,479 non-hydrogen atoms performed by the program XPLOR, has led to an R-factor of 18.3%. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 12 publications
0
46
0
1
Order By: Relevance
“…In addition, the loop that connects the R and S domains (the arm) is ordered in C subunits but disordered in A and B subunits. A similar structural organization was observed in Turnip crinkle virus (TCV) (50) and Carnation mottle virus (CarMV) (25), which are two other species in the Tombusviridae family and whose capsid structures have been solved to a resolution of ϳ3 Å. All three viruses share a phylogenetically related CP, produce virions with capsids possessing Tϭ3 icosahedral symmetry (9), and are ϳ350 Å in diameter.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the loop that connects the R and S domains (the arm) is ordered in C subunits but disordered in A and B subunits. A similar structural organization was observed in Turnip crinkle virus (TCV) (50) and Carnation mottle virus (CarMV) (25), which are two other species in the Tombusviridae family and whose capsid structures have been solved to a resolution of ϳ3 Å. All three viruses share a phylogenetically related CP, produce virions with capsids possessing Tϭ3 icosahedral symmetry (9), and are ϳ350 Å in diameter.…”
mentioning
confidence: 55%
“…This high degree of virion stability raises the question of how the intracellular environment triggers disassembly or minimally exposes the genome for translation. Structural analyses of several plant viruses have revealed that maintenance of a stable capsid conformation is dependent on the presence of divalent cations bound to the capsid (25,33,36). It has been a longstanding hypothesis that swelling and other conformational changes induced by ion extraction from virions are critical for a productive viral life cycle (13).…”
Section: ؉mentioning
confidence: 99%
“…Data collection on crystals of Carnation Mottle Virus [10] illustrates very well the advantage of using slort wavelengths. Some data had previously been collected on these crystals on film with 1.488 Α radiation and under these conditions crystals could withstand only one or two exposures.…”
Section: Selected Resultsmentioning
confidence: 93%
“…The structure was easily solved by molecular replacement and refined with 5-fold non-crystallographic symmetry restraints to an R factor of 18%. The model comprises 7 479 protein atoms [10].…”
Section: Selected Resultsmentioning
confidence: 99%
“…Hasta el momento se conoce con bastante detalle la estructura de los viriones formados por 5 miembros del género: el CarMV [Morgunova et al, 1994], el CPMoV [Ke et al, 2004], el HCRSV Doan et al, 2003;Cheng et al, 2009a], el MNSV [Wada et al, 2008] y el TCV [Hogle et al, 1986]. Estos estudios han permitido conocer mejor la interrelación entre las distintas subunidades de la CP e inferir la forma en la que tiene lugar el ensamblaje de las partículas [Ke et al, 2004].…”
Section: Género Carmovirusunclassified